Exploring cleaner routes of Alumina Production: Thermodynamic Simulation of Pedersen Process and CO2 Capture Integration via Calcium Looping - Sáez-Guinoa, Javier; Romeo, Luis Miguel; Llera Sastresa, Eva (Jornada de Jóvenes Investigadores del I3A, 2024)
Alumina industry stands out as a significant contributor to mineral scarcity because of the generation of bauxite residue during its production process. This study explores an alternative route to produce alumina: the Pedersen process. A thermodynamic simulation and an energy optimization are implemented to avoid bauxite residues and reach the goal of zero CO2 emissions.